USE OF X-RAYS AND QGIS® SOFTWARE TO EVALUATE DETERIORATED WOOD IN MARINE ENVIRONMENTS - Lins, Tarcila Rosa da Silva; Moura, Marks Melo; Müller, Ana Claudia de Paula; Lana, Paulo da Cunha; Rocha, Márcio Pereira da (Floresta, 2021)
The objective of this work was to propose a nondestructive method to identify and quantify the damage caused by marine borers in wood structures. First, a test specimen was submerged in an estuarine environment for 120 days. Radiography was then applied to detect and evaluate the attack by marine borers. Two methods of evaluation were performed with the images to compare them. The first assessment was carried out using the QGIS® geoprocessing program for the treatment of images as a tool, which made it possible to identify and quantify the damage (in cm²). The second evaluation followed the method indicated in EN 275 (1992), which suggests a visual assessment, based on X-ray images, classified according to a template provided in the standard. Although the method using the image treatment by QGIS® is an estimate, it has the advantage of providing a numerical result, in contrast to the visual analysis, which is not as accurate due to its subjectivity. Besides this, the treatment of the images allowed good visualization of the damage to the specimen. The findings indicated that QGIS® can be used as a complement to the method proposed by EN 275 (1992).